A inibição da recaptação de dopamina pelo GBR12909 como um possível modelo animal de mania: aspectos comportamentais, farmacológicos e neuroimunológicos - Juliana dos Reis Bastos (2015)
Bipolar disorder (BD) is a psychiatric disorder featured by the occurrence of mania and depression episodes. The pharmacological treatment consists in mood stabilizers, including lithium and valproate. In addition, antipsychotic drugs, such as aripiprazole, have been used as adjuvant therapies in the treatment of maniac episodes. Aripiprazole efficacy, however, has not been validated in animal models predictive for mood stabilizers drugs. The inhibition of dopamine transporter by GBR12909 was recently proposed as an animal model of mania, since it mimics the psychomotor agitation observed in patients undergoing a BD associated maniac episode. Moreover, several studies have been supporting the idea that dopaminergic neurotransmission plays a role in BD pathophysiology. Therefore, the aims of the current work were: (i) validate the effect of GBR12909 as a predictive model for mania-like behaviour; (ii) quantify alterations in neuroinflammatory parameters in brain areas related to symptoms displayed by bipolar patients and (iii) test the hypothesis that Aripiprazole inhibits the behavioral effects of GBR12909. GBR12909 administration at 15 mg/kg induces hyperlocomotion in Swiss mice, in the protocols with and without habituation. GBR12909 also leads to an increase in the cytokine IL-4, IL-10 and IL-17 levels in striatum, IL-6 and IFN- in striatum and hippocampus and decreased IL-6 levels in prefrontal cortex, 24 hours after administration. Acute lithium carbonate injection (12.5; 25; 50 e 100 mg/kg) inhibited GBR12909 effect at the higher doses, whereas sodium valproate (75; 150 e 300 mg/kg) failed to mimic this effect. Aripiprazol, however, prevented this effect at the doses of 0.1; 1 and 10 mg/kg. In conclusion, GBR12909 administration seems to be a useful model of mania-like behaviour, since it mimics some changes observed in patients undergoing a mania state and induces neuroinflammatory alterations potentially associated with BD physiopathology. Moreover, lithium and the antipsychotic aripiprazol inhibit the effect of GBR12909, in agreement with its effectiveness in this disorder.